Artificial Insemination in rabbits - El Gaafary M.N.; Marai I.F.M. (Rabbit production in hot climates, 1994)
The success of artificial insemination (AI) technique in rabbits depends on various factors that act in a complex way. These include type of semen, supplementation of semen with some stimulators, method of inducing ovulation and doe status. Rabbit semen has been successfully stored on liquid state for short periods of time (6 h for fresh and 48 h for refrigerated) without serious loss of its fertilizing ability. However, there are few recent information on the comparative values of different diluents. The efficiency of AI with frozen semen did not reach the level of fresh semen. This is because rabbit spermatozoa are relatively sensitive to cryoprotectants added before freezing. Cryoprotectants containing hydroxil groups are relatively less effective than those containing amide or methyl groups. Supplementation of rabbit semen with PGE2 improved fertility. However, PGF2alpha produced a detrimental effect. Insemination with cooled rabbit semen supplemented with 5mM theophylline was as effective as fresh semen and improved the kindling rate by about 22.6 per cent when compared to the non-supplemented cooled semen. The development of a practical method for induction of ovulation repeatedly with gonadotropin releasing hormone without antigenecity have led to a commercial application of its use. Conception rate of the virgin doe is higher compared to that of the primiparous and multiparous animals. Younger animals are shown to be less fertile than those of 1.0 - 1.5 years, but conception rate decreased in older animals. Conception rate in lactating does is lower than in dried ones. Does with high live weight also have high conception rates. However, further studies should be carried out before final conclusions can be drawn.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)